2015
DOI: 10.1111/head.12628
|View full text |Cite
|
Sign up to set email alerts
|

Visual Snow in Migraine With Aura: Further Characterization by Brain Imaging, Electrophysiology, and Treatment – Case Report

Abstract: The visual snow and loss of habituation ability in migraine associated with occipital bending can be improved with lamotrigine treatment. This report may provide new insights on "visual snow" pathophysiology in migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 16 publications
(47 reference statements)
3
70
0
Order By: Relevance
“…Currently the VS pathophysiology and treatment options are under investigation . In our previous case report, we have demonstrated that loss of habituation ability in a VS patient with migraine was improved with lamotrigine treatment . There was a comment whether loss of habituation was due to visual snow or migraine to our case report .…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…Currently the VS pathophysiology and treatment options are under investigation . In our previous case report, we have demonstrated that loss of habituation ability in a VS patient with migraine was improved with lamotrigine treatment . There was a comment whether loss of habituation was due to visual snow or migraine to our case report .…”
Section: Introductionmentioning
confidence: 51%
“…The discrepancy may be because of the different methodology in these studies . In our study, 10 blocks of 100 responses to repetitive pattern stimuli were recorded and averaged . The habituation response was calculated according to the 10th‐1st block response, which is compatible with 1000 VEP responses per eye.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, VEPs to repeated stimulation are often potentiated, or increased, in patients with migraine . Consistent with this idea, a recent study reported VEP potentiation associated with visual snow . However, these results have been questioned due to the patient's prior history of migraine with aura, as well as more general concerns about the reliability of VEP habituation in migraine …”
mentioning
confidence: 89%
“…Therefore, we believe that the potentiation effect on rVEPs that the authors described cannot be unequivocally attributed to VS but rather seems to be related to the underlying MWA. We suggest that this finding should be more prudently confirmed on a larger number of patients, possibly trying to make a distinction between the subgroups of VS with or without comorbid migraine.…”
mentioning
confidence: 78%